Biomechanical analysis technique choreographic movements (for example, "grand battman jete") - N.P. Batieieva (H.S. Skovoroda Kharkov National Pedagogical University, 2015)
Purpose : biomechanical analysis of the execution of choreographic movement "grand battman jete". Material : the study involved students (n = 7) of the department of classical choreography faculty of choreography. Results : biomechanical analysis of choreographic movement "grand battman jete" (classic exercise), obtained kinematic characteristics (path, velocity, acceleration, force) of the center of mass (CM) bio parts of the body artist (foot, shin, thigh). Built bio kinematic model (phase). The energy characteristics - mechanical work and kinetic energy units legs when performing choreographic movement "grand battman jete". Conclusions : It was found that the ability of an athlete and coach-choreographer analyze the biomechanics of movement has a positive effect on the improvement of choreographic training of qualified athletes in gymnastics (sport, art), figure skating and dance sports.